2017
DOI: 10.3390/coatings7090143
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Elastic Characteristics of an Aluminum Thin-Film Using Laser Optical Measurement Techniques

Abstract: Abstract:The increase of a surface area-to-volume ratio with the reduction of material dimensions significantly alters the characteristics of materials from their macroscopic status. Therefore, efforts have been made to establish evaluation techniques for nanoscale films. While contact mechanics-based techniques are conventionally available, non-contact and nondestructive methods would be preferable in case damages left on a sample after testing are not desirable, or an in situ assessment is required. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The thickness of all three films was around 100 nm. Values obtained by LAW are compared with the values given by other authors [13][14][15][16][17] and in case of Al and Ti also with the results from nanoindentation. Table 1 shows that, the values of Young's modulus obtained by LAW correspond to those obtained from nanoindentation and are within the range reported in literature.…”
Section: Thin Film Characterization -Young's Modulus Evaluationmentioning
confidence: 73%
“…The thickness of all three films was around 100 nm. Values obtained by LAW are compared with the values given by other authors [13][14][15][16][17] and in case of Al and Ti also with the results from nanoindentation. Table 1 shows that, the values of Young's modulus obtained by LAW correspond to those obtained from nanoindentation and are within the range reported in literature.…”
Section: Thin Film Characterization -Young's Modulus Evaluationmentioning
confidence: 73%
“…In Ref. 38 a useful summary of the elastic modulus of Al thin films with different thicknesses collected by several authors is reported; it is worth mentioning that, with few exceptions (33 and 102 GPa), the values were found between 55 and 81 GPa with considerable scatter. In this work, the average value of the elastic modulus for all of the samples is equal to 79 GPa, with a standard deviation of 7.7 GPa.…”
Section: Resultsmentioning
confidence: 99%
“…In Ref. 38, the elastic modulus of Al-coated films (with Al thickness>150 nm) was evaluated by means of two laser optical measurement techniques: a test approach based on a microscale beam combined with FEA and a picosecond ultrasonics wave propagation analysis. No investigations have been found in the literature, to the authors’ knowledge, on bulge mechanical characterization of PI film and Al-coated PI film with thicknesses<150 nm, which is relevant for filter applications on soft x-ray/extreme ultraviolet (EUV) astrophysics space missions.…”
Section: Introductionmentioning
confidence: 99%